Pengaruh ROM Aktif-Asistif Dengan Spherical Grip Terhadap Kekuatan Genggam Tangan Dan Rentang Gerak Sendi Pasien Stroke Non-Hemoragik - Eko Anggoro Santoso; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Journal of Medical Practice and Research, 2025)
Non-hemorrhagic stroke is a leading cause of long-term disability, frequently resulting in upper-extremity muscle weakness, particularly reduced handgrip strength and limited joint range of motion. These impairments substantially diminish patients’ functional capacity and independence. Active-assisted Range of Motion (ROM) exercises combined with spherical grip training are believed to stimulate neuromuscular function and enhance muscle strength through repetitive motor practice. This study employed a pre-experimental two-group pretest–posttest design involving 36 respondents (18 in the intervention group and 18 in the control group) at RSUD Dr. H. Soewondo Kendal. Participants were selected using purposive sampling. Muscle strength was measured using Manual Muscle Testing (MMT), while joint range of motion was assessed with a goniometer. Data were analyzed using the Wilcoxon and Mann–Whitney tests. The findings demonstrated a significant improvement in handgrip strength and in most joint range-of-motion parameters following active-assisted ROM therapy with spherical grip (p ≤ 0.05). In contrast, the control group showed no statistically significant changes. These results indicate that active-assisted ROM therapy with spherical grip is effective in improving handgrip strength and joint range of motion in patients with non-hemorrhagic stroke. Therefore, this intervention is recommended as an integral component of nursing rehabilitation programs to enhance motor function and improve post-stroke quality of life